A Multidisciplinary Approach to Empowering Coastal Women’s Groups: Packaging Innovation, Product Shelf Life, and Nutritional Information for Seafood Products - Nurul Chamidah; Tri Budi Prasetyo; Rizki Budhi Suhara; Ari Yulistianingsih; Daduk Merdika Mansur; Wildan Haflah Nabil (Golden Ratio of Community Services and Dedication, 2026)
This community service program aimed to develop innovative packaging for seafood products as an effort to increase the added value, shelf life, and marketing potential of Ambulu Village’s flagship products in Losari District, Cirebon Regency. The program partners were Family Welfare Empowerment (PKK) cadres who manage Kafe Jukung, a culinary business unit that offers various seafood dishes and still depends on the availability of fresh ingredients from local fishers’ catches. The activity was conducted over six months, from June to November 2025, through several stages: preliminary observation, product development by an interdisciplinary team, packaging design, product shelf-life testing, nutritional content analysis, training in packaging techniques, and sustainability evaluation. The results show that three main dishes—blekutak masak hitam, sweet-and-sour shrimp, and smoked sembilang fish mangut—were successfully developed into ready-to-eat products with innovative packaging that is informative, hygienic, and visually attractive. Shelf-life testing showed that the products remained suitable for consumption after sterilization, storage, and reheating. Nutritional analysis showed that all three products met the criteria for low-fat claims. Training and mentoring improved the PKK cadres’ skills in standardized packaging processes, enabling them to perform the procedures independently. This program strengthened partner capacity and opened marketing opportunities for seafood products as distinctive Ambulu souvenir foods with strong competitiveness.